Деякі особливості етнічної і громадянської свідомості української та російської молоді (на матеріалі етносоціологічного опитування) - Москаленко, Н.; Снєжкова, І.; Чебанюк, О. (Народна творчість та етнографія, 2006)
This article arose as the result of mutual Ukrainian-Russian research project “The image of Ukraine and Russia in the Ukrainian and Russian youth's notion”, which was carried out with the support of Ukraine National Academy of Sciences and Russian State Scientific Fund in 2005. This article is dedicated to the sociological research of the Ukrainian the Russian youth’s national and social consciousness.